Archaeological trial excavations at Frankopan Square in Senj (In situ, 2024)
Archaeological trial excavations were conducted at Frankopan Square in Senj in two archaeological campaigns in 2022 to determine the likelihood that the site holds archaeological potential. The results of trial excavations indicate that those areas of Frankopan Square that were not affected by recent constructions and burials in the 20th century contain rich cultural layers that date from Late Antiquity to the Modern Period.
Keywords: Senj; Frankopan Square; Late Antiquity; Modern era